Características sociodemográficas relacionadas ao nível de conhecimento e prática de idosos para prevenção do pé diabético - Santos, Maria Alcina Batista dos (2022)
Type 2 diabetes is one of the most common metabolic syndromes in the elderly. Among its main complications is the diabetic foot, which consists of lesions that cause tissue destruction of the feet resulting from diabetic neuropathy. Objective: To evaluate the knowledge and practices of the elderly in the prevention of diabetic foot. Materials and methods: this is a descriptive, exploratory, transversal and quantitative study. Data collection was performed through a validated questionnaire containing sociodemographic data and knowledge and practice in diabetic foot. Pearson's chi-square was used to associate these variables, considering a significance level (p<0.05). Results: We found a predominance of young elderly, female, married, income and low education. Participants achieved medium to high scores in all categories. No significant associations were identified. Conclusion: The results presented in this study allowed us to emphasize the importance of developing strategic educational measures in order to train diabetics for self-care through knowledge about the disease and its complications.